Pengorganisasian dalam Perspektif Al-Qur’an dan Hadits (Kajian Al-Qur’an dan Hadits Tematik) - Endah Tri Wisuda Ningsih (HUMANISTIKA : Jurnal Keislaman, 2017)
The existence of the organization is very important for humans because it is a tool to achieve the goal of life he wanted. Through the organization, people will work, and shows its existence in order to achieve satisfaction with what has become the goal. To achieve the productivity and satisfaction in the work that, then an organization requires management as a tool or the art of managing the organization to be run efficiently (efficient), effective (effective), and can achieve the expected goals.